Burnout Mediation and Psychological Resilience Moderation between Role Conflict and Turnover Intention among Generation Z - Sunardi Ginting; Krisdayanti (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The increasing participation of Generation Z in the workforce has created new challenges for organizations, particularly due to their tendency to experience role conflict arising from the need to balance work and academic responsibilities. This study aims to examine the direct, mediating, and moderating relationships among role conflict, burnout, psychological resilience, and turnover intention among Generation Z employees who work while attending college. A quantitative approach was employed, involving 435 Generation Z respondents in West Kalimantan who were simultaneously working and pursuing higher education. Data were collected via five-point Likert scale questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS. The results indicate that role conflict has a positive and significant effect on burnout, while burnout has a positive and significant effect on turnover intention. Role conflict does not have a direct effect on turnover intention. Rather, burnout fully mediates this relationship. Psychological resilience positively influences turnover intention and mitigates the effects of role conflict on burnout and burnout on turnover intention; however, it does not moderate the relationship between role conflict and turnover intention.